The handbook of competency mapping understanding, designing and implementing competency models in organizations - Sanghi, Seema 1961- (SAGE Publications, Inc., 2016)
This thoroughly revised third edition helps human resource managers and professionals understand, develop, manage and map competencies within their organizations. It presents the complete know-how of developing competency framework in detail. In this edition, several chapters have been expanded to provide a greater understanding of business strategies, environmental imperatives and the changing role of HR as a strategic partner. Developed over years of research and consultancy experience, three new chapters on 'Competency-based Interviewing', 'Writing Competencies' and 'Competency Framework for Academic Institutions' have been added